Preparation of socially maladjusted youth located in youth educational centres for self-sufficient living - Mielczarek, Mirosław (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2020)
The article is of a theoretical and research nature. The theoretical part outlines the specificity of a social rehabilitation centres for minors and refers to the definition of self-sufficiency. The subject of the research was the empowerment of juveniles staying in youth educational centres. Their aim was to find out the answer to the problem: what methods and forms of work are used by youth educational centres to prepare minors for a self-sufficient life after leaving them in the following spheres: family, professional, social and civic? The project was carried out in three selected youth educational centres. The data was obtained using the pedagogical monograph method, for which the document analysis technique was selected, supplemented with an original data sheet acting as a research tool. The research was conducted in the mainstream of the qualitative approach identified with the interpretative paradigm, which allowed for the abandonment of hypotheses.